Digital Forensics threatscape and best practices - Sammons, John (Syngress is an imprint of Elsevier, 2016)
This book surveys the problems and challenges confronting digital forensic professionals today, including massive data sets and everchanging technology. You will learn the basics of cryptocurrencies (like Bitcoin) and the artifacts they generate; discover why examination planning matters and how to do it effectively; incorporate behaviorial analysis into your digital forensics examinations; stay updated with the key artifacts created by the latest Mac OS, OS X 10.11, El Capitan. It discusses the threatscapes and challenges facing mobile device forensics, law enforcement, and legal cases; the power of applying electronic discovery workflows to digital forensics; shows the value of and impact of social media forensics. --